Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.255
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Affordances of Slack Integrations and Their Actualization Within Enterprises - Towards an Understanding of How Chatbots Create Value

Abstract: The rise of chatbots poses new possibilities to link social interactions within instant messengers with thirdparty systems and business processes. While many companies use chatbots within the enterprise in the form of Slack apps and integrations, little is known about their affordances. Grounded in a qualitative research endeavour, we conducted 12 explorative interviews in 8 organizational settings to inductively gain rich contextual insights. Our results reveal 14 functional affordances in 4 categories, eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
0
14
0
6
Order By: Relevance
“…Exploring Slack chatbots, Stoeckli et al [32] found functional affordances related to receiving information and outcomes of automated workflows, functional affordances related to getting and setting triggers and reminders, functional affordances related to queries and invocations within Slack channels and functional affordances related to the enrichment of messages We want to build on this study of CA affordances and respond to Leidner et al [16] call to explore the effects of the actualisation of CA affordances on the customers and human employees.…”
Section: Theory Of Technology Affordancementioning
confidence: 99%
“…Exploring Slack chatbots, Stoeckli et al [32] found functional affordances related to receiving information and outcomes of automated workflows, functional affordances related to getting and setting triggers and reminders, functional affordances related to queries and invocations within Slack channels and functional affordances related to the enrichment of messages We want to build on this study of CA affordances and respond to Leidner et al [16] call to explore the effects of the actualisation of CA affordances on the customers and human employees.…”
Section: Theory Of Technology Affordancementioning
confidence: 99%
“…Uma das tecnologias inovadoras utilizadas no meio online, nas interfaces entre empresas e consumidores, são os chatbots. Como uma forma de autoatendimento e de interação entre humanos e máquina (Brandtzaeg & Følstad, 2018;Kurachi, Narukawa, & Hara, 2018), os chatbots têm ganhado atenção por automatizar as conversas e as trocas de informações em que a máquina processa o conteúdo da fala para responder adequadamente os humanos Stoeckli, 2018). A comunicação com o consumidor e o aumento da produtividade e eficiência de processos internos e externos das organizações são algumas das formas que o chatbot está sendo aplicado, criando um canal de comunicação acessível a qualquer momento que permite a coleta dos dados das interações e das opiniões dos clientes para um melhor relacionamento.…”
Section: Lista De Figurasunclassified
“…Quadro 1 -Definições de chatbot Autor Definição Ciechanowski et. al (2018) O sistema do chatbot é um programa de software que interage com os usuários utilizando a linguagem natural Chakrabarti e Luger (2015) O chatbot é um programa de software que se envolve em conversas artificiais através de entradas de texto Khan e Das (2018) Um programa de computador que processa linguagem natural inserida por um usuário e que gera respostas relativas e inteligentes que são respondidas ao usuário Shawar e Atwell (2005) O chatbot é um sistema de conversação por máquina que interage com usuários humanos via linguagem de conversação natural Stoeckli (2018) Sistemas, ferramentas e roteiros integrados e direcionados pela conversação na forma de mensagens instantâneas, o qual pode ocorrer unilateralmente ou bilateralmente Fonte: Desenvolvido pela autora (2019) De forma geral, as diferentes definições estão alinhadas ao indicarem o elemento artificial, a linguagem natural e a interação do chatbot com um humano. Dentre as definições apresentadas no Quadro 1, todas indicam a função de realizar conversações com uma máquina do chatbot e o seu componente tecnológico.…”
Section: Chatbotunclassified
See 2 more Smart Citations